PROFIL PERKEMBANGAN MOTORIK HALUS DAN KREATIVITAS ANAK KELOMPOK B DALAM KEGIATAN COOKING CLASS - Anggraheni, Ika (Thufuli, 2019)
The use of hands, fingers and eye coordination are indicators of the success of fine motor development. Creativity in children's work is the result of fine motor skills.This research is a research with descriptive quantitative research. Data analysis techniques use descriptive with percentage. The study was conducted at Probolinggo Pembina State Kindergarten, especially for children aged 5-6 years (group B) totaling 30 children. Based on the results of these studies, this study is concluded as follows. In the variable fine motor ability indicator 1: the majority of children get a score of 4 as many as 16 children (53%). Indicator 2: the majority of children get a score of 4 which is as many as 15 children (50%). In indicator 3: the majority of children get a score of 4 which is as many as 18 children (60%). Indicator 4: the majority of children get a score of 4 as many as 20 children (67%). Indicator 5: the majority of children get a score of 4, namely 19 children (63%).The results on the variables of creativity development include the following. In indicator 1: the majority of children get a score of 4 which is as many as 15 children (50%). Indicator 2: the majority of children get a score of 4, which is 21 children (70%). Indicator 3: the majority of children get a score of 4, which is 16 children (53%). Indicator 4: the majority of children get a score of 4 which is as many as 18 children (60%). Indicator 5: the majority of children get a score of 4 as many as 20 children (67%).